2017
DOI: 10.1007/s41686-017-0010-4
|View full text |Cite
|
Sign up to set email alerts
|

Mobile, but Are We Better? Understanding Teacher’s Perception of a Mobile Technology Integration Using the Unified Theory of Acceptance and Use of Technology (UTAUT) Framework

Abstract: As the popularity of mobile technology rises, there is an increased emphasis to integrate these devices into the classroom. While some research has investigated its effectiveness, further research is needed to understand why teachers adopt these tools to improve teaching. Using the Unified Theory of Acceptance and Use of Technology (UTAUT), this formative assessment used an explanatory mixed-methods approach to identify the barriers and challenge teachers face in adoption. Themes of the qualitative data focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
4
8
0
Order By: Relevance
“…That means H 1 has rejected. These results have supported previous studies such as [10], [31]. A study by [31] found that the use of MT failed to improve teacher performance in shaping more meaningful teaching.…”
Section: B Assessment Of Structural Modelsupporting
confidence: 88%
See 4 more Smart Citations
“…That means H 1 has rejected. These results have supported previous studies such as [10], [31]. A study by [31] found that the use of MT failed to improve teacher performance in shaping more meaningful teaching.…”
Section: B Assessment Of Structural Modelsupporting
confidence: 88%
“…This situation led to H 3 being rejected. These findings are the same as studies conducted by [10], [34]. A study by [34] on 359 samples stated that teachers find it difficult to gain support from the surrounding community in integrating technology in school environments, especially in developing countries.…”
Section: B Assessment Of Structural Modelsupporting
confidence: 80%
See 3 more Smart Citations